Critical Analysis of Javanese Epistemology and Its Relevance to Science Development in Indonesia - Reno Wikandaru; Shely Cathrin; Erwinsyah Satria; Dian Rianita (Humaniora, 2020)
Humans have developed science to understand the phenomena they face in their lives. As such, the development of science is inexorably linked with epistemology because it emphasizes the question of truth—the focus of epistemology. The development of science and knowledge has been influenced by specific interests, motives, needs, and historic/cultural backgrounds. To ensure that science is developed in a manner best suited for Indonesian society, such development must be rooted in extant Indonesian cultural values, such as those found in Javanese culture. This study attempts to formulate Javanese epistemology as a basis for scientific development in Indonesia. It finds, first, that knowledge is known as “kawruh” among the Javanese people; second, knowledge is not always limited to the cognitive dimension; and third, a specific criterion for truth is harmony, or “pener”. Javanese people consider “rasa” capable of bringing humans to the supreme knowledge. Although objective knowledge exists, every individual achievement of reality is different. Javanese people consider the validity or truthfulness of statements/actions rooted in their harmony with the empirical rational principle of truth and the existing order, following the adage “bener tur pener”.